Study on Wellness Programs Offered by the Health Insurance Companies (International Journal of Preventive Medicine and Health (IJPMH), 2024)
Introduction: Wellness is the act of ensuring a healthy lifestyle regularly. It is a multidimensional phenomenon. There are wellness providers such as hospitals, insurance companies, diagnostics, and wellness firms. It focuses on the wellness programs offered by Indian and International health insurance companies. Method: Descriptive and cross-sectional study on the wellness programs delivered by health insurance companies. The survey was conducted on the outlook of customers for the wellness programs offered by insurance companies. Result: List of wellness programs offered by various health insurance companies. The determination of the interest of consumers in wellness programs and rewards related to it. Discussion: Wellness programs include fitness challenges, modifications in diet and lifestyle, goal-based exercises, and healthy living. This paper discusses wellness initiatives, benefits, and regulations of wellness programs for insurance companies. Application: A comprehensive wellness plan for health insurance companies to increase the well-being of their customers. Conclusion: Both the insured and the insurer get benefit from the wellness initiatives. Wellness programs keep individuals healthy and therefore reduce the possibility of future claims. This increases the revenue of insurance companies.